ANALISIS NILAI SAHAM DENGAN PENDEKATAN ABSOLUTE VALUATION DAN RELATIVE VALUATION PADA PERUSAHAAN PENAMBANGAN - Meiliana Jaunanda (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
Investment in Indonesia is getting more advanced from year to year. This can be seen from the IHSG has increased every year accompanied by improving economic growth in various sectors. One of the sectors that an important role in the development of the country is the mining sector. The mining sector has a high capitalization value and dominant in Indonesia and abroad. This is enough to pay attention to investors to invest their capital, but before buying and selling a stock, investors conduct an analysis first whether the shares invested are overvalued, fairvalued and undervalued. This study uses relative valuation techniques to value stocks using price book value (PBV) and price earning ratio (PER) proxies and determines whether the stock is overvalued, fairvalued and undervalued. Sampling was carried out at mining companies which consecutively distributed dividends during the 2015-2019 period. The result of this research is that ADRO, both PER and PBV in 2019, was undervalued. KKGI both PER and PBV in 2019 has been overvalued. ITMG, MYOH and PTBA under PER are undervalued and PBV overvalued.Arista, Desy. 2012. "Analisis Faktor -Faktor Yang Mempengaruhi Return Saham (Kasus pada Perusahaan Manufaktur yang Go Public di BEI Periode Tahun 2005-2009)". Jurnal Ilmu Managemen dan Akutansi Terapan, Vol 3 Nomor 1 , Mei. 2012. hal. 1-15.Astohar. 2010. "Pengaruh Return On Asset, Debt to Equity Ratio, Price To Book Value, Dan Earning Per Share Terhadap Return Saham Pada Perusahaan Manufaktur Di Bursa Efek Indonesia". Eksplanasi Volume 5 Nomor 2 Edisi Oktober. 2010.Brigham, E. F., & Houston, J. F. (2018). Dasar- Dasar Manajemen Keuangan Edisi 14 Buku 1. Jakarta: Salemba EmpatFabozzi, Frank. J. (2000). Manajemen Investasi. Jakarta : Salemba EmpaMarkowitz, H.M. (1952), â€œPortfolio selectionâ€, Journal of Finance, Vol. 7 No. 1, pp. 77-91, doi: 10.1111/j. 1540-6261.1952.tb01525.xRose, Westerfield, Jaffe & Jordan. 2012. Fundamentals of Corporate Finance. New York: McGraw-Hill.Ross SM. Stochastic Processes. Second Edition. Berkeley: University of California; 1996Sulistyorini (2009), Analisis Kinerja Portofolio Saham Dengan Metode Sharpe, Treynor & Jensen, Universitas Diponegoro, SemarangSutrisno. (2017). Manajemen Keuangan Teori, Konsep dan Aplikasi Edisi-2. Yogyakarta: Ekonisia.Tandelilin, E. (2017). Pasar Modal Manajemen Portofolio & Investasi. Depok: PT Kanisius.Yanawati, P.N.W. and dan Abundanti, N. (2014), â€œKinerja Portofolio Saham pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesiaâ€, E-Jurnal Ekonomi dan Bisnis Universitas Udayana, Vol. 3 No. 1, pp. 83-99